More on the Disposable Lens - Belanger, G.M. (Canadian Journal of Optometry, 2026)
From time to time, we find that one of our Editorials provokes a reaction. Quite frankly, we thrive on it because it means we're being read. A few issues ago, for example, we ran an Editorial on the disposable lens ("The Disposable Soft Lens - Boon or Disaster". CJO•RCO. Autumn. 1987) and it has proven to be one of those rare occasions in which a chord - both abrasive and responsive - was struck in many of our readers. We heard from members of the profession and the ophthalmic industry, expressing both approval and disapproval of our opinions.